Colonial impact in Daniel Defoe’s Robinson Crusoe and Jonathan Swift’s Gulliver’s Travels - Zannat, Fatema Tul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.